Przewrót majowy jako etap w narastaniu w polskim życiu politycznym tendencji skrajnych - Kawalec, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
In contrast to the reality of totalitarian dictatorships, Piłsudski and his collaborators did not outlaw their political opposition. Nevertheless, the latter lost the possibility of returning to political power through elections; besides, the ruling regime which was based mainly on the military and bureaucratic forces attempted to make life diffi cult for political parties it considered adversarial by applying various tools of harassment, the oppressiveness of which was gradually increasing. Not all the nuances of the changed circumstances were instantly visible. The election of 1928, and later of 1930, demonstrated the efficiency of administrative pressures and sometimes of ordinary falsifying of the results; in 1930 it turned out that the authorities did not hesitate to direct progressively harsher administrative repressions against energetic opposition activists. Plagued by organizational splits which were initiated either by the people of pro-government orientation or by the followers of political extremism, feeling the consequences of the withdrawal of people dependent upon the state public school teachers, officials, etc. from political activity, the opposition parties closed their ranks and tightened their organizational structures. In the impoverished country with underdeveloped labor market the youth understandably constituted a growing group of dissatisfied citizens. Unable to perceive any prospects for themselves, they naturally turned to the opposition for which the youth’s energy and radicalism provided obvious opportunities. The youth participation made its impression upon the activities of all political movements. Generally speaking, young people were very much skeptical about parliamentarianism, seeing the Sejm as a basically powerless institution constantly dismissed by the government camp’s propaganda. They also did not possess personal experiences which might have helped them develop different sensibilities. On the inside of the respective parties, the youth’s position was quickly gaining more strength; the parliamentary activists who dominated before 1926 were often incapable of adapting to the altered rules of political game. Their dependence on the parliamentary rostrum which was constantly losing signifi cance led to their marginalization, especially after 1935 when the altered Electoral Bill deprived the opposition parties of the possibility to participate in the elections. This occurrence deepened the scale of processes happening inside the parties, accelerated the personal changes in their leadership and forced them to modify their tactics. The characteristic occurrence, observable in the activity of all political circles, was a growing ideologization of their practices and programs. It was partly a consequence of relegating the parties to the opposition role and of depriving them of contact with practical politics, partly a result of the need to provide people with powerful motivation to participate in politics under difficult conditions when engagement in political life on the side of particular parties might have caused them grave complications in everyday life
Keywords: May 1926 coup d’etat